2003
DOI: 10.1046/j.1439-054x.2003.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

The Guidelines for 'Non-Restorative Sleep': Relevance for the Diagnosis and Therapy of Insomnia. Die Leitlinie "Nicht-erholsamer Schlaf": Relevanz fur Diagnostik und Therapie der Insomnie

Abstract: Summary Concerning the diagnosis and therapy of insomnia, a shift of paradigm has taken place in recent years. Traditionally, treatment has focused on improving night sleep, i. e. shortening sleep latency and prolonging total sleep time. Modern approaches aim at improving or restoring the recuperative value of sleep and ensuing daytime functioning on a social, psychological and professional level. Based on the guidelines for ‘non‐restorative sleep’ of the German Society of Sleep Research and Sleep Medicine, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…A growing body of evidence supports causal pathways associating contextual features with a variety of outcomes such as cardiovascular and -metabolic diseases, depression or unhealthy lifestyles [1]. In spite of its high prevalence in the general population [2,3], insomnia has not been much of interest in epidemiological neighbourhood studies [4]. Only a few studies have explored whether social neighbourhood characteristics might be associated with sleep problems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence supports causal pathways associating contextual features with a variety of outcomes such as cardiovascular and -metabolic diseases, depression or unhealthy lifestyles [1]. In spite of its high prevalence in the general population [2,3], insomnia has not been much of interest in epidemiological neighbourhood studies [4]. Only a few studies have explored whether social neighbourhood characteristics might be associated with sleep problems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Germany has demonstrated that patients with Global Sleep Dissatisfaction (GSD) were two times more likely to report excessive daytime sleepiness compared with insomnia patients without GSD (Ohayon and Zulley, 2001). In concordance with these investigations the German Society of Sleep Medicine has published a formal consensus that defined non‐restorative sleep – a reflection of impaired sleep quality according to DSM‐IV and ICD‐10 criteria – to be the key syndrome in the clinical algorithm to diagnose and treat sleep disorders (Riemann et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic, epigenetic as well as neuroendocrine mechanisms may drive the vulnerability or resilience, respectively, towards certain sleep phenotypes and, subsequently, mood disorders by differentially shaping the sensitivity towards prenatal/early-life stress and/or negatively influencing early brain developmental processes and/or favoring such personality, temperament, character and attachment style that may predispose to mood disorders.Consequently, assessing and targeting insomnia and abnormal circadian synchronisation as potentially modifiable behaviors by providing correctly timed cues should be a priority in daily clinical practice in order to intervene in the developmental trajectory of mood disorders by providing prevention and early treatment(Kaplan and Harvey 2013;Dallaspezia and Benedetti 2011;Hickie et al 2013;Dallaspezia et al 2015;Harvey et al 2015;Jansson-Fröjmark and Norell- Clarke 2016;Riemann D, Baglioni et al 2017). Particularly, Cognitive Behavioral Therapy for Insomnia (CBT-I) has shown great effects, which is the first line treatment for insomnia(Riemann D, Baum et al 2017, Riemann D, Baglioni et al 2017, could be ideal for the prevention of mood disorders and it has been shown to improve not only insomnia but mood disorders' trajectory when used as add-on within the context of mood disorder treatment in adults(Kaplan and Harvey 2013;Jansson-Fröjmark and Norell-Clarke 2016;Riemann D, Baglioni et al 2017) but also children and adolescence(Paine and Gradisar 2011;de Bruin et al 2014; Adolescent Sleep Working Group 2014; American Academy of Pediatrics 2014;Clarke et al 2015;Marx et al 2017). Also the therapy for abnormal timing of circadian rhythm has been shown to improve the trajectory of mood disorders in adults(Dallaspezia and Benedetti 2011;Hickie et al 2013;Dallaspezia et al 2015;Harvey et al 2015).…”
mentioning
confidence: 99%